Efficient alkaline hydrogen evolution on atomically dispersed Ni-NxSpecies anchored porous carbon with embedded Ni nanoparticles by accelerating water dissociation kinetics - Lei, Chaojun; Wang, Yu; Hou, Yang; Liu, Pan; Yang, Jian; Zhang, Tao; Zhuang, Xiaodong; Chen, Mingwei; Yang, Bin; Lei, Lecheng; Yuan, Chris; Qiu, Ming; et al. (Energy and Environmental Science, 2019)
Developing inexpensive and efficient electrocatalysts for hydrogen evolution reaction (HER) during alkaline water electrolysis is crucial for renewable and sustainable energy harvesting. Herein, we report a novel hybrid electrocatalyst comprising atomically dispersed Ni-N x species anchored porous carbon (Ni-N-C) matrix with embedded Ni nanoparticles for HER. This new catalyst is synthesized via pyrolysis of hydrothermally prepared supermolecular composite of dicyandiamide and Ni ions followed by an acid etching treatment. The achieved hybrid exhibits superior catalytic performance toward HER with a small overpotential of 147 mV at 10 mA cm -2 and a low Tafel slope of 114 mV dec -1 , comparable to those of state-of-the-art heteroatom-doped nanocarbon catalysts and even outperforming other reported transition-metal-based compounds in basic media. Experimental observations and theoretical calculations reveal that the presence of Ni nanoparticles can optimize surface states of Ni-N x active centers and reduce energy barriers of dissociated water molecules, which synergistically improve OH - adsorption and promote HER kinetics. When served as electrodes for both cathode and anode, an alkaline water electrolyzer could afford a current density of 10 mA cm -2 at a low cell voltage of 1.58 V, rivalling the sufficiently high overpotentials of integrated Pt/C-Ir/C benchmark electrodes.
CRIS-Team Scopus Importer:2023-03-20